Techniques used in teaching KBSR English in rural schools: A case of ERaIL teachers - Shabdin, Ahmad Affendi; Ibrahim, Azian; Hashim, Hajah Jahara; Ishak, Mohd. Noor; Mohd Abdullah, Mohd Nordin; Mohamad, Mutiara; Omar, Noor Hadfizah; Awang Hashim, Rosna; Syed Sahil, Syahrifah Azizah; Wan Din, Wan Zalina (Universiti Utara Malaysia, 1995)
This study is based on a survey done on 43 KBSR teachers of English in the rural district of Padang Terap/Pendang, as a follow-up to the training sessions in which the teachers were exposed to various techniques in teaching English. The study which focuses on three areas: vocabulary, reading comprehension and oral instructions, tries to find out which of the techniques exposed during the training the teachers prefer. The results of this survey showed that three techniques of teaching vocabulary were favoured among the six techniques discussed during the training. As for reading comprehension, most of the respondents had used the suggested stages, which were demonstrated and discussed during the training sessions. In teaching oral instructions, approximately half of the sample used the sequence demonstrated in the training while the rest were flexible in their choice of which sequence they thought was the best.